Prediction of crack tip opening displacement of fibre composites - Srivastava V.K. (My University, 2025)
The fracture behaviour of single edge notched unidirectional glass fibre reinforced epoxy resin composites under tensile loading was investigated. Load-elongation curves were obtained for crack length varying from 4, 6, 8, 10 and 12mm and different fibre volume fractions of 0.48, 0.502 and 0.525. The results show that the fracture strength and fracture toughness are dependent on the crack length. Crack tip opening displacement (CTOD) can be estimated with the use of fracture toughness in mode-I. © 1992.